An Inside look at microfinance - Sophaseila, Sakett (KDI School, 2011)
This thesis attempts to extract from the micro nance literature a package of mea-sures, or index, which can be used by microfinance institutions (MFIs) to gauge their success as financial institutions, as well as their broader societal impact as welfare organizations. The author turns to the major sources of data that are generally accepted in microfinance and did not conduct primary data collection himself, given what is available today. We learned that MFIs, unlike any traditional financial service providers such as banks and insurance companies, are largely unregulated and therefore tend to use a variety of non-standardized measures to assess their success and sustain-ability. Furthermore, we show that these institutions cannot easily trade those measures that track institutional success, for those that measure the community impact as a result of borrowing money and planting a small business or SME, since a number of confounding factors make direct correlation dificult. Finally, we propose a measure toolkit by applying the simplified Balanced Scorecard (simplified BSC) framework to measure MFI success matrices. We use the MFI data that reports on the nancial status of the organization, its internal business practices, the rate of borrower success, and lessons learned. Moreover, the MFI assumed to impact the borrower community at large can use the same framework to aggregate these data across borrower communities and monitor them along with certain health and welfare data to infer a degree of behavioral impact. Then, we apply the proposed measure toolkit on a real case MFI in Cambodia in order to assess the appropriateness of the matrices.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: MFI(Microfinance Institutions)